Blockade of Kv1.3 Potassium Channels Inhibits Differentiation and Granzyme B Secretion of Human CD8+ T Effector Memory Lymphocytes - Hu, Lina; Wang, Tongguang; Gocke, Anne R.; Nath, Avindra; Zhang, Hao; Margolick, Joseph B.; Whartenby, Katharine A.; Calabresi, Peter A. (PLOS ONE, 2013)
Increased expression of the voltage-gated potassium channel Kν1.3 on activated effector memory T cells (TEM) is associated with pathology in multiple sclerosis (MS). To date, most studies of Kν1.3 channels in MS have focused on CD4+ TEM cells. Much less is known about the functional relevance of Kv1.3 on CD8+ TEM cells. Herein, we examined the effects of Kν1.3 blockade on CD8+ T cell proliferation, differentiation into cytotoxic effector cells, and release of granzyme B (GrB), a key effector of CD8+ T cell-mediated cytotoxicity. We confirmed the expression of Kv1.3 channels on activated human CD8+ T lymphocytes by immunofluorescent staining. To test the functional relevance of the Kv1.3 channel in CD8+ T cells, we inhibited this channel via pharmacological blockers or a lentiviral-dominant negative (Kv1.xDN) approach and determined the effects of the blockade on critical pathogenic parameters of CD8+ T cells. We found that blockade of Kv1.3 with both lentivirus and pharmacologic agents effectively inhibited cytotoxic effector memory cells’ proliferation, secretion of GrB, and their ability to kill neural progenitor cells. Intriguingly, the KvDN transduced T cells exhibited arrested differentiation from central memory (TCM) to effector memory (TEM) states. Transduction of cells that had already differentiated into TEM with KvDN led to their conversion into TCM. CD8+ TEM have a critical role in MS and other autoimmune diseases. Our present results indicate a critical role for Kv1.3 in the conversion of CD8+ T cells into potential pathogenic effector cells with cytotoxic function.